Vegetative growth of Umbrella Leaf Palm, Johannesteijsmannia lanceolata in Angsi Forest Reserve, Malaysia - Rozainah, M. Z.; Sinniah, U. R. (Ecoprint: An International Journal of Ecology, 2010)
A study of an acaulescent palm, Johannesteijsmannia lanceolata J. Dransfield was carried out in Angsi Forest Reserve Negeri Sembilan Malaysia for a period of 19 months A total of 32 adults, 24 juveniles and 32 seedlings from 3 different plots were censused every two weeks. The results showed that the average numbers of new leaves entering the crown with in the study period (19months) were: 3.3, 2.6 and 1.3 for 2.1, 1.6 and 0.8 leaves per year for adult juvenile and seedling, respectively. From the calculation it was discovered that the time spent by each leaf in the crown before it died was 8.8 years for adult and 8.4 years for juvenile. Key words: Johannesteijsmannia; Growth rate; Vegetative phenology; Arecaceae doi: 10.3126/eco.v12i0.3190 Ecoprint: An International Journal of Ecology 12: 11-20, 2005